COUNTER HEGEMONY TERHADAP LUNTURNYA SIKAP NASIONALISME MELALUI PENDIDIKAN BERBASIS KARAKTER PADA MAHASISWA PPKN ANGKATAN 2024 UNIVERSITAS JAMBI - Rizki Akbar; Hajri, Priazki; Opeska, Yuslistia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the phenomenon of the declining sense of nationalism among university students due to the increasingly massive influence of globalization and foreign cultures. This condition can be seen from students’ low understanding of national values, lack of interest in local culture, and weak implementation of nationalist attitudes in daily life. This study aims to identify the forms of counter-hegemony against the decline of nationalism through character-based education and to examine the role of character-based education as a counter-hegemony strategy among the 2024 cohort of PPKn students at Universitas Jambi. This research was conducted at the Civic Education Study Program (PPKn), Faculty of Teacher Training and Education, Universitas Jambi. The informants in this study consisted of PPKn lecturers, PPKn students from the 2024 cohort, and the study program administration. The research employed a descriptive qualitative approach. Data collection techniques included observation, interviews, and documentation. The data analysis techniques consisted of data reduction, data presentation, and conclusion drawing using source, technique, and time triangulation to test the validity of the data. The results of the study indicate that the sense of nationalism among the 2024 cohort of PPKn students at Universitas Jambi is still relatively low, influenced by the dominance of global culture and the lack of internalization of national values. The forms of counter-hegemony identified include the improvement of students’ critical awareness toward the influence of foreign cultures, efforts to maintain national identity, and participation in activities that reflect nationalist values. Character-based education plays a major role as a primary strategy in strengthening nationalism through the cultivation of moral values, habituation of positive attitudes, and exemplary behavior within the academic environment. This research is expected to contribute to strengthening character education as a strategic effort to rebuild nationalism among the younger generation.